Long-term effect of early-life stress from earthquake exposure on working memory in adulthood - Li N (Dove Medical Press, 2015)
Na Li,1-3* Yumei Wang,1-3* Xiaochuan Zhao,1-3 Yuanyuan Gao,1-3 Mei Song,1-3 Lulu Yu,1-3 Lan Wang,1-3 Ning Li,1-3 Qianqian Chen,1-3 Yunpeng Li,1-3 Jiajia Cai,1-3 Xueyi Wang1-31Department of Psychiatry, The First Hospital of Hebei Medical University, 2Mental Health Institute of Hebei Medical University, 3Brain Ageing and Cognitive Neuroscience Laboratory, Hebei, People’s Republic of China *These authors contributed equally to this work Objective: The present study aimed to investigate the long-term effect of 1976 Tangshan earthquake exposure in early life on performance of working memory in adulthood.Methods: A total of 907 study subjects born and raised in Tangshan were enrolled in this study. They were divided into three groups according to the dates of birth: infant exposure (3–12 months, n=274), prenatal exposure (n=269), and no exposure (born at least 1 year after the earthquake, n=364). The prenatal group was further divided into first, second, and third trimester subgroups based on the timing of exposure during pregnancy. Hopkins Verbal Learning Test-Revised and Brief Visuospatial Memory Test-Revised (BVMT-R) were used to measure the performance of working memory. Unconditional logistic regression analysis was used to analyze the influential factors for impaired working memory.Results: The Hopkins Verbal Learning Test-Revised scores did not show significant difference across the three groups. Compared with no exposure group, the BVMT-R scores were slightly lower in the prenatal exposure group and markedly decreased in the infant exposure group. When the BVMT-R scores were analyzed in three subgroups, the results showed that the subjects whose mothers were exposed to earthquake in the second and third trimesters of pregnancy had significantly lower BVMT-R scores compared with those in the first trimester. Education level and early-life earthquake exposure were identified as independent risk factors for reduced performance of visuospatial memory indicated by lower BVMT-R scores.Conclusion: Infant exposure to earthquake-related stress impairs visuospatial memory in adulthood. Fetuses in the middle and late stages of development are more vulnerable to stress-induced damage that consequently results in impaired visuospatial memory. Education and early-life trauma can also influence the performance of working memory in adulthood. Keywords: Tangshan earthquake, early life stress, working memory, chronic effect